Landscapes of devotion: the settings of St Swithun's early uitae. (24th July 2017) - Lorden, Jennifer A.
Abstract: Although post-Conquest uitae of St Swithun narrate the saint's earthly life, the original tenth-century accounts relate only his post-mortem miracles, professing ignorance of his life as bishop of Winchester. Most of the miracles in these pre-Conquest uitae take place in or in some way revolve around the site of the saint's relics at the Old Minster, Winchester. Late-tenth-century Winchester, along with the Benedictine Reformers who had taken up residence there, thus figures prominently in these miracle stories; indeed, Winchester comes to be the true protagonist of Swithun's pre-Conquest uitae . Moreover, each of Swithun's three pre-Conquest hagiographers – Lantfred, Wulfstan the Precentor and Ælfric – writes a different Winchester according to his relationship to that place. This phenomenon illuminates these writers' differing relationships to the Benedictine Reform, as well as how the Reformers sought to write their own histories.